Validity and Test–Retest Reliability of the Dutch Modified Perceived Deficits Questionnaire to Examine Cognitive Symptoms in Women with Chronic Whiplash, Chronic Idiopathic Neck Pain, and Fibromyalgia. - Lenoir, D.; De Pauw, R.; Ickmans, K.; Schumacher, C.; Timmers, I.; Kregel, J.; Coppieters, I. (Pain Practice, 2018)
Abstract: Introduction: Until now, only reliability and validity of the English version of the modified Perceived Deficits Questionnaire (mPDQ) have been investigated. Objective: The aim of this study was to translate the mPDQ into Dutch and evaluate its validity and reliability as an assessment tool for self‐perceived cognitive problems in patients with chronic whiplash‐associated disorders (CWAD), chronic idiopathic neck pain (CINP), and fibromyalgia (FM). Methods: A case–control study was performed with a volunteer sample of 13 women with CWAD, 18 with CINP, and 33 with FM, and 33 women who were healthy and free of pain. The mPDQ was first translated into Dutch, and its test–retest reliability, internal consistency, and discriminative power were examined. Results: The intraclass correlation coefficients were higher than 0.74. Cronbach's α values ranged between 0.71 and 0.95. Total mPDQ scores were significantly higher (P < 0.017) in FM and CWAD patients compared to healthy controls. Furthermore, participants performed the Stroop task and the psychomotor vigilance task (PVT), 2 neuropsychological computer‐based cognitive performance tests. Correlations between the mPDQ total score and the cognitive performance tests were evaluated. Significant moderate to high correlations were found in all study samples between total mPDQ score and objective cognitive tests (Spearman correlation coefficient = 0.35 to 0.80; P < 0.05). Conclusion: Therefore, the Dutch version of the mPDQ showed high test–retest reliability and high internal consistency, and was able to distinguish CWAD and FM patients from healthy controls. Perspective: This article presents the validity and test–retest reliability of the Dutch mPDQ. This measure could help clinicians who seek a reliable and user‐friendly way to assess cognitive symptoms in chronic pain patients.